An evaluation of the community-school program from the standpoint of teachers, principals and supervisors - Serion, Josefina R. 1915- (1953)
The immediate purpose of this study was to evaluate the community school program from the standpoint of teachers, principals, and supervisors.
Mimeographed.
Vita.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Community and school